Pemaknaan terhadap Status Berbahasa Minangkabau dalam Facebook - Roza Saidi Naali; Rona Almos; Bahren Bahren; Herry Nur Hidayat (Jurnal Elektronik WACANA ETNIK, 2018)
This article describes the meaning contained Facebook status uses Minangkabau language. Data were collected through the searching method. Each sorted word is sought by referents so that can be interpreted and classified according to their form and type.The results show besides four types of diction; diction related to scientific and popular words, diction related to conversation words, diction related to slang, and diction related to a foreign language, also found three types of meanings; conceptual meaning, connotative meaning, associative meaning.